2006
DOI: 10.1016/j.jvs.2005.12.010
|View full text |Cite
|
Sign up to set email alerts
|

Experimental pulmonary embolism: Effects of the thrombus and attenuation of pulmonary artery injury by low-molecular-weight heparin

Abstract: Persistent pulmonary artery distention by an inert material is sufficient to invoke significant inflammation and intimal hyperplasia independent of the thrombus itself. Compared with nontreated PE, LMWH is the only therapy associated with a significant reduction in late intimal hyperplasia and, with the exception of TGF-beta, lower profibrotic growth-factor production.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 27 publications
2
14
0
Order By: Relevance
“…The most significantly regulated genes in a differential manner were related to cardiomyopathy and inflammation. Our results are consistent with recent studies reporting significant changes of pulmonary artery during PTE[5153]. …”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…The most significantly regulated genes in a differential manner were related to cardiomyopathy and inflammation. Our results are consistent with recent studies reporting significant changes of pulmonary artery during PTE[5153]. …”
Section: Discussionsupporting
confidence: 94%
“…It was reported more than 30 years ago that white blood cell count was significantly associated with incidence and mortality of coronary heart disease[58]. Recently, both epidemiological and clinical studies have shown that inflammatory and immune response play important roles in pulmonary embolism (PE): gene expression of type I and II IFN was significantly associated with PE[59]; protein levels of C-reactive protein (CRP), fibrinogene, and leukocyte count were associated with chronic obstructive pulmonary disease (COPD)[60]; gene expression profiling of lung tissues in PE has identified differentially expressed genes enriched in inflammatory, defense and immune response pathways[53]. …”
Section: Discussionmentioning
confidence: 99%
“…In the case of silicone embolism, the mediation of immunological agents is supported by findings in experimental animals, in which the introduction of solid silicone emboli has been followed by increased levels of inflammation mediators and hyperplasia of arterial intima [26]. In the present case, the triggering of inflammatory mechanisms by the presence of silicone in small blood vessels is suggested by the patient's high platelet count and sedimentation rate [27].…”
Section: Discussionsupporting
confidence: 65%
“…28 We measured proinflammatory IL-1β and profibrotic cytokine IL-13 to test this hypothesis in our model. We found no differences in vein wall IL-1β (Fig 5, A ), but intrathrombus IL-1β was significantly reduced in the WT mice treated with LMWH at days 2 and 6 and in PAI-l −/− mice treated with LMWH at day 6 ( P < .05; n = 4–5; Fig 5, B ).…”
Section: Resultsmentioning
confidence: 99%